The Silent Cry: Empathy and Elegy in Mavis Gallant's Novels - Smythe, Karen (Studies in Canadian Literature, 1990)
In Mavis Gallant's novels -- Green Water, Green Sky, "Its Image on the Mirror," and A Fairly Good Time -- structure and language, the emotional and empathic elements of the fiction, serve to involve the reader in the experiences of each mournful character. When silence seems to be the only option for a character, Gallant either uses a narrator to elegize on behalf of that character (as in Green Water, Green Sky), or provides the character with a displaced form of self-expression (as in "Its Image on the Mirror" and A Fairly Good Time). In all of these novels, then, the silent cry of each protagonist is ultimately voiced. Yet, there is a judgmental quality to Gallant's fiction, in that the uninvolved reader is implicated alongside the non-comprehending, unempathetic characters in Gallant's critiques. In the end, we are urged to take responsibility for our own readings, both of the literary realities of the fiction and of the literal reality it serves to illuminate -- we are urged to listen for that silent cry.